Anti‐inflammatory role of obestatin in autoimmune myocarditis. (January 2016) - Pamukcu, Ozge; Baykan, Ali; Bayram, Latife Cakir; Narin, Figen; Cetin, Nazmi; Narin, Nazmi; Argun, Mustafa; Ozyurt, Abdullah; Uzum, Kazim
Summary: Obestatin is a popular endogeneous peptide, known to have an autoimmune regulatory effect on energy metabolism and the gastrointestinal system. Studies regarding the anti‐inflammatory effects of obestatin are scarce. The aim of this study was to show the anti‐inflammatory effect of obestatin in an experimental model of autoimmune myocarditis in rats. Experimental autoimmune myocarditis was induced in Lewis rats by immunization with subcutaneous administration of porcine cardiac myosin, twice at 7‐day intervals. Intraperitoneal pretreatment with obestatin (50  μ g/kg) was started before the induction of myocarditis and continued for 3 weeks. The severity of myocarditis was evidenced by clinical, echocardiographic and histological findings. In addition, by‐products of neutrophil activation, lipid peroxidation, inflammatory and anti‐inflammatory cytokines were measured in serum. Obestatin significantly ameliorated the clinical and histopathological severity of autoimmune myocarditis. Therapeutic effects of obestatin in myocarditis were associated with reduced lipid peroxidation, suppression of polymorphonuclear leukocyte infiltration and enhancement of glutathione synthesis, inhibition of serum inflammatory and activation of anti‐inflammatory cytokines. Histopathologically, the left ventricle was significantly dilated, and its wall thickened, along with widespread lymphocytic and histocytic infiltration. The myocardium was severely infiltrated with relatively large mononuclear cells. These histopathological changes were observed in lesser degrees in obestatin‐treated rats. This study demonstrated a novel anti‐inflammatory effect of obestatin in an experimental model of autoimmune myocarditis. Consequently, obestatin administration may represent a promising therapeutic approach for myocarditis and dilated cardiomyopathy in the future.